Comparison of small molecules VEGFR inhibitors in the treatment of renal cell carcinoma - Jie Yi Tan; Aadya Jaipuria; Ronny Priefer (Universitas Ahmad Dahlan, 2023)
Vascular endothelial growth factors receptors (VEGFR) inhibitors play a vital role in the treatment of renal cell carcinoma. These are small molecules that predominantly exhibit anti-angiogenesis activity in conjunction with other anti-tumor effects. These drug therapies are approved for the use in patients as frontline agents or adjuvant therapy in renal cell carcinoma. However, VEGFR inhibitors are associated with undesirable adverse events, with some having a more manageable toxicity profile compared to others. As a result, choice of treatment poses a challenge for healthcare providers and patients. Nonetheless, these agents demonstrate improved disease/progression free survival (DFS/PFS) values and remain a critical component in the treatment of kidney cancer.